1988
DOI: 10.1111/j.1439-0507.1988.tb04405.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Production as a Typing Tool for the Dermatophytes

Abstract: Summary:  A typing scheme for dermatophytes, based on their antibiotic production, is proposed and evaluated. Zusammenfassung:  Ein Typisierungsschema für Dermatophyten, das auf deren Antibiotika‐Produktion beruht, wird vorgeschlagen und bewertet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…However, the two species of T. mentagrophytes (S2 and S4) gave two unknown compounds, which do not match with Betina classification (Betina, 1973) of the thin layer antibiotic analysis (results not shown). The work done before by Hammadi et al (1988) on the same species showed the production of penicillin-like substances by the same species, the only differences for the work before is the temperature of incubation. For the previous work, the incubation temperature was 30 o C, however the temperature of the present work is 32 o C. Therefore, it can be deduced that incubation temperature has an effect on secondary metabolites production during the fermentation (Youssef et al, 1979).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…However, the two species of T. mentagrophytes (S2 and S4) gave two unknown compounds, which do not match with Betina classification (Betina, 1973) of the thin layer antibiotic analysis (results not shown). The work done before by Hammadi et al (1988) on the same species showed the production of penicillin-like substances by the same species, the only differences for the work before is the temperature of incubation. For the previous work, the incubation temperature was 30 o C, however the temperature of the present work is 32 o C. Therefore, it can be deduced that incubation temperature has an effect on secondary metabolites production during the fermentation (Youssef et al, 1979).…”
Section: Resultsmentioning
confidence: 92%
“…Antibacterial screening of dermatophytic fungi metabolites. Days S1 S2 S3 S4 S5 S6 S7 S8 S9 S10 1 0 0 0 0 0 0 0 0 0 0 2 Hammadi et al, 1988) and incubated at 30°C in an orbital incubator at 140 rpm. After 10 days of incubation, the growth media was extracted with an equal volume of acetone.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations